2021
DOI: 10.1002/ejoc.202100011
|View full text |Cite
|
Sign up to set email alerts
|

Excited‐State 2,3‐Dichloro‐5,6‐dicyano‐1,4‐benzoquinone (DDQ*) Initiated Organic Synthetic Transformations under Visible‐Light Irradiation

Abstract: Dedicated to Prof. Shunichi Fukuzumi on the occasion of his 70 th birthday.The one-electron oxidizing capacity of 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) improves significantly by visible-light excitation. The exited-state DDQ (DDQ*) even converts benzene, fluoroarenes, heteroarenes, benzyls, and olefins into their corresponding radical cations as well as chloride and other anions into their radicals. These reactive intermediates have been utilized for the generation of CÀ C and CÀ X (N, O, or Cl) bond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 58 publications
(157 reference statements)
0
31
0
4
Order By: Relevance
“…However, the substantial luminescence quenching effect displayed by the styrene derivative (Figure 1) and comparatively diminished reactivity of the electron‐deficient double‐bonds towards the nitration reaction advocate for an electron transfer photooxidation of the olefins (Path A) as the major pathway. Finally, regeneration of the DDQ photocatalyst proceeds through aerial oxidation with the assistance of TBN [11a] . Presumably, in both pathways, the preferential E ‐stereoselectivity observed may be due to a higher stability of the E ‐isomer over that of the Z olefin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the substantial luminescence quenching effect displayed by the styrene derivative (Figure 1) and comparatively diminished reactivity of the electron‐deficient double‐bonds towards the nitration reaction advocate for an electron transfer photooxidation of the olefins (Path A) as the major pathway. Finally, regeneration of the DDQ photocatalyst proceeds through aerial oxidation with the assistance of TBN [11a] . Presumably, in both pathways, the preferential E ‐stereoselectivity observed may be due to a higher stability of the E ‐isomer over that of the Z olefin.…”
Section: Methodsmentioning
confidence: 99%
“…We initiated the investigation by analyzing the optoelectronic properties of the organo‐photocatalyst DDQ and the redox potential of the reactant olefins. Although the synthetic utility of quinone derivatives as photocatalyst is underexplored, recent studies revealed that DDQ can participate in the photoinduced electron transfer process and can be a superior photo‐oxidant [11a] . Photo‐excited DDQ* possesses high reduction potential [ E 1/2 (DDQ*/DDQ .− )=3.18 V vs SCE] with a prolonged triplet excited‐state lifetime of 2.4 ms.…”
Section: Methodsmentioning
confidence: 99%
“…The second subcategory of e‐PRC, dubbed “recycling e‐PRC”, involves the turnover of a photocatalyst that is a known photoredox catalyst (PRCat) in PRC, and that is a colored species in its ground, neutral state. Figure 19 depicts the structures of PRCats used in recycling e‐PRC; their photophysical properties are thoroughly detailed elsewhere [2c,e, 38, 55] . In recycling e‐PRC, the available “redox window” is no wider than it is for PEC.…”
Section: Photocatalyst Electro‐recyclingmentioning
confidence: 99%
“…DDQ as an eutral photocatalyst is ap owerful oxidant in its long-lived triplet excited state (+ 3.18 Vv s. SCE). [38] Despite its absorbance maxima at % 400 nm, DDQ is successfully photoexcited with longer wavelength blue (455 nm) light. Prior to any contemporary reports of recycling e-PRC,K çnigsg roup achieved the photocatalytic oxidation of electron-deficient arenes by 3 DDQ*i nt he presence of tert-butyl nitrite and molecular oxygen, [39] which was reviewed previously.…”
Section: Photocatalyst Electro-recyclingmentioning
confidence: 99%
“…Die zweite Unterkategorie von e‐PRC, die als “Recycling‐e‐PRC” bezeichnet wird, umfasst den Umsatz eines Photokatalysators, des PRC, dessen neutraler Grundzustand eine farbige Spezies darstellt. Abbildung 19 zeigt die Strukturen von PRC‐Katalysatoren, die bei Recycling e‐PRC verwendet werden; ihre photophysikalischen Eigenschaften werden an anderer Stelle ausführlich beschrieben [2c,e, 38, 55] . Beim Recycling‐e‐PRC ist das verfügbare “Redoxfenster” nicht größer als bei der PRC.…”
Section: Photokatalysator‐elektrorecyclingunclassified